Analysis of piston head metallurgy / Izaham Ismail, Mohd. Rahmat Abd. Jalil and Fazli Nordin - Ismail, Izaham; Abd. Jalil, Mohd. Rahmat; Nordin, Fazli (2002)
In this project paper, we try to understand and investigate about wear mechanism. As an Automotive student, we prefer pistons as an experiment sample. We comparing the result of surface roughness to define whether there is a wear in each part of piston; top, middle and skirt. Maybe there no slightly change in microstructure and hardness value due to time running for samples are not quite longer. For that reason, we took the used piston from workshop to see result of surface roughness, hardness and their microstructure. We hope at the end of our project, we should know what is wear mechanism and how it occurs due to operation of 2 stroke internal combustion engine.